Global access to COVID-19 vaccines: a scoping review of factors that may influence equitable access for low and middle-income countries - Elin Hoffmann Dahl; Elizabeth F Peacocke; Lieke Fleur Heupink; Katrine Frønsdal; Lumbwe Chola (BMJ Open, 2021)
Objective To identify the factors contributing to equitable access to COVID-19 vaccines for low and middle-income countries (LMIC).Methods We conducted a scoping review following the guidelines for Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews and a five-stage framework for scoping studies. We performed systematic searches for published peer-reviewed literature in five databases: Medline, Embase, Web of Science, Global Index Medicus and COVID-19 Evidence Epistemonikos (August 2020, updated May 2021).Results Systematic selection according to predefined criteria resulted in the final inclusion of 45 peer-reviewed articles, with no limitations on study design or publication type. We derived four key factors that potentially influence equitable access to COVID-19 vaccines in LMICs: (1) collectively agreed global mechanisms or frameworks; (2) bilateral purchasing, contracting, and vaccine prices; (3) vaccine manufacturing that is supported by sharing know-how; and (4) countries’ strength in implementing vaccination programmes.Conclusions This scoping review highlights the ongoing challenges for the international community in ensuring equitable access to COVID-19 vaccines for LMICs. The literature suggests that vaccine manufacturing can influence the supply of vaccines, as can the role of patent holders who can influence global governance through their role in the distribution of COVID-19 vaccines. Our findings indicate that including the principles of equitable access throughout vaccine research and development, procurement, scale-up and distribution processes can support equitable access for LMICs. Advances made with mRNA vaccines may have additional benefits in relation to expanding the manufacturing of other vaccine. Finally, the exploration and scale-up of such capacities of LMICs are likely to prove to be a valuable investment, even after the pandemic.